Dacogen administration experience for treatment of patients with myelodisplastic syndrome and chronic myelomonocytic leukemia - S. V. Gritzaev; K. M. Abdulkadirov; D. I. Shikhbabaeva; I. S. Martinkevich; S. A. Tiranova (Онкогематология)
Dacogen treatment results of 8 MDS patients and 2 CMML patients (a course dose — 100 mg/m2) are presented. Hematological response according to modified IWG criteria (complete remission - 2 pts, bone marrow remission — 1 pts, disease stabilization — 4 pts) has been established in 70% of patients. Complete cytogenetic response has been achieved in one patient with secondary MDS and multiple chromosomal aberrations after 2 therapy courses. Complications because of which intercourse intervals elongated are registered in 3 patients. The obtained data demonstrated efficacy of Dacogen treatment for high risk MDS and CMML patients.